Conditions of Possibility of Knowledge and Spaces of Logic Possibility - Angélica María Rodríguez Ortiz (Pensamiento. Revista de Investigación e Información Filosófica, 2020)
Knowledge construction has been a topic of interest to the philosophy of language, given the need to validate the aletic and apophantic form of statements that constitute such a discourse. For a long time, Classical logic has been in charge of validating the judgments of fact that constitute science; however, in the last few decades, logic modal studies have gained particular strength, with which it is intended to examine, among others, the epistemic statements and beliefs of cognizants from the use of modal operators, among them, those that set the boundaries of the theory of possible worlds. This article aims to show the role of beliefs, language and logic in the conditions of possibility of knowledge, based on a review of the relevance of the theory of possible worlds and the spaces of logical possibility in the Construction and analysis of the scientific discourse.